Las series chilenas en la era del streaming: Panorama y desafíos para la formación ciudadana - Lorena Antezana Barrios (Les Cahiers ALHIM)
The consolidation of streaming platforms and their strategies to capture new markets have provided an interesting window for the exhibition of local productions, but also a challenge for producers. In this text we present an overview of the evolution, lessons and adjustments that the national industry has had to make to adapt to the demands and expectations of the audiences of these platforms and we highlight the genres that have been most strengthened in this instance: historical and thriller. Both, being based mostly on real events, can be used as input for citizen training by presenting stories that, despite the universality they must have, speak of Chileans, their past, their idiosyncrasy and ultimately their particularities.